Vision enhancement using stereoscopic telepresence for remotely operated underwater robotic vehicles - Iastrebov, Viatcheslav (2020)
Remotely operated Underwater Robotic Vehicles (URV) are widely used for subsea tasks such as cleaning, repair and inspection of long objects such as pipelines. The ability to perform such inspections by a remotely located human pilot, over extended periods, is highly desirable. Due to underwater currents and the inability to maintain a fixed distance from the object, produces a constantly varying image for the observer. Incorporation of stereoscopic imaging, with the option of maintaining a constant image size, was perceived to be desirable. This effect was implemented by dynamic compensation of the camera zoom, and shown to negate the negative motion effects and allowed the operator to perform close inspection for extended periods of time. This paper describes the design, structure, and preliminary evaluation of an experimental Telepresence Viewing System (TVS) for Underwater Robotic Vehicle (URV) to enhance the observation capabilities of its remote pilot during an inspection task. The Telepresence Viewing System enables an automatic projection of suitably prepared and adapted underwater stereoscopic video images from the video cameras of the URV, into the operator’s visual field. The processed images aid the coupling of the operator’s vestibular and kinesthetic sensations to the visual information from the URV.